2022
DOI: 10.1097/jom.0000000000002666
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function in Factory Workers Exposed to Heat Stress

Abstract: Factory workers exposed to heat stress maintained kidney function after a 2-year follow-up period. Cystatin C is a better kidney function marker than creatinine in the cross-shift assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Throughout the different study types, a coherent picture of the social and economic impacts of heat exposure in the workplace emerges, highlighting the main pathways for heat-related productivity losses. One pathway is in common with the general population and is related to the increased risk of acute heat-related illnesses and deaths ( 1 ) and the emergence of chronic illnesses consequences such as renal impairment ( 5 , 6 ). Underlying biological mechanisms include thermoregulatory failure with cardiovascular fatigue and respiratory distress, dehydration with progressive kidney dysfunction in case of sustained chronic exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the different study types, a coherent picture of the social and economic impacts of heat exposure in the workplace emerges, highlighting the main pathways for heat-related productivity losses. One pathway is in common with the general population and is related to the increased risk of acute heat-related illnesses and deaths ( 1 ) and the emergence of chronic illnesses consequences such as renal impairment ( 5 , 6 ). Underlying biological mechanisms include thermoregulatory failure with cardiovascular fatigue and respiratory distress, dehydration with progressive kidney dysfunction in case of sustained chronic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Workers are normally healthier than the general population, but they, especially those severely exposed and engaged in heavy workloads, may be equally affected by heat stress when the thermoregulatory capacity of the body is disrupted, and physiological pathways resulting in heat-related illness, acute outcomes (e.g., myocardial infarction), or exacerbations of pre-existing diseases (e.g., cardiovascular and respiratory outcomes) are activated ( 2 ). Individuals working in the heat are also prone to physical strength losses and cognitive function impairments, leading to work-related injuries ( 3 ), missed workdays, and productivity reductions ( 4 ) and, in the long term, may develop chronic kidney impairment ( 5 , 6 ). Health and productivity outcomes related to heat strain have a huge impact in terms of social and economic costs on the different actors involved ( 7 ): the workers themselves due to the temporary or permanent health and quality of life impairments and missed wages, the farm or factory due to necessity of maintaining production despite employees absences or output reductions, the healthcare system due to the healthcare expenditures due to workers seeking care, the social security or insurance system due to reimbursements to laborers for injuries, permanent disability, or occupational diseases, and the whole country or region in terms of reductions of the gross domestic product due to production losses in specific economic sectors.…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study that included factory workers exposed (and not exposed) to heat stress, it was found that the exposed workers had a greater decline in creatinine-based eGFR during the work shift 23 . However, after 2 years of follow-up, kidney function was maintained 24 .…”
Section: Occupational Risk Factors For Ckdntmentioning
confidence: 94%
“…Em um estudo piloto que incluiu trabalhadores industriais expostos (e não expostos) ao estresse térmico, constatou-se que os trabalhadores expostos apresentaram um declínio maior na TFGe baseada em creatinina durante o turno de trabalho 23 . Entretanto, após dois anos de acompanhamento, a função renal estava mantida 24 .…”
Section: Estresse Térmicounclassified